Key Determinants of Residential Apartment Buying Behaviour in Noida Post-COVID-19 - Sharan, Dayal (Digital Repository of Theses - SSBM Geneva, 2025)
Background: The COVID-19 pandemic has changed consumer lifestyle and priorities, especially in urban residential real estate. These shifts have influenced housing demand, buyer expectations, and preferences in emerging urban centres like Noida. Objectives: This study explores the key factors influencing the buying behaviour of customers purchasing residential apartments in Noida after COVID-19. It aims to assess how population density, build quality, and connectivity affect decision-making in the post-pandemic housing market. Methodology: The research adopts a quantitative approach grounded in the Theory of Planned Behaviour. It collected data from 212 respondents through structured questionnaires. Statistical analysis was conducted to identify correlations and significance levels among various influencing factors. Findings: The study reveals a shift in buyer preferences toward low-density environments, higher construction quality, robust healthcare access, and remote work-compatible spaces. Physical and digital connectivity has gained prominence, alongside considerations like safety, hygiene, and sustainable design. Implications: The findings provide critical insights for developers, urban planners, and policymakers. Stakeholders can better address emerging urban housing needs by aligning development strategies with post-pandemic buyer expectations.